2017
DOI: 10.1146/annurev-cellbio-100616-060439
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Mechanistic Insights into Protein Translocation

Abstract: Many proteins are translocated across the endoplasmic reticulum (ER) membrane in eukaryotes or the plasma membrane in prokaryotes. These proteins use hydrophobic signal sequences or transmembrane (TM) segments to trigger their translocation through the protein-conducting Sec61/SecY channel. Substrates are first directed to the channel by cytosolic targeting factors, which use hydrophobic pockets to bind diverse signal and TM sequences. Subsequently, these hydrophobic sequences insert into the channel, docking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
267
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(269 citation statements)
references
References 93 publications
2
267
0
Order By: Relevance
“…Examples include hexameric ATPases, such as the p97 ATPase (Cdc48 in yeast), which extracts proteins from membranes or tight complexes, the Clp's and the ATPases of the 26S proteasome, which push polypeptides into a proteolytic chamber, and the NSF protein, which disassembles SNARE complexes involved in membrane fusion (for review, see Zhao et al, 2007;Bodnar & Rapoport, 2017;Ye et al, 2017;Yedidi et al, 2017). Another important member of this ATPase family is SecA, which translocates polypeptides through the plasma membrane in bacteria (for review, see Corey et al, 2016;Rapoport et al, 2017;Cranford-Smith & Huber, 2018). SecA acts a monomer and uses the energy of ATP hydrolysis to move its substrates through the protein-conducting SecY channel (Economou & Wickner, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Examples include hexameric ATPases, such as the p97 ATPase (Cdc48 in yeast), which extracts proteins from membranes or tight complexes, the Clp's and the ATPases of the 26S proteasome, which push polypeptides into a proteolytic chamber, and the NSF protein, which disassembles SNARE complexes involved in membrane fusion (for review, see Zhao et al, 2007;Bodnar & Rapoport, 2017;Ye et al, 2017;Yedidi et al, 2017). Another important member of this ATPase family is SecA, which translocates polypeptides through the plasma membrane in bacteria (for review, see Corey et al, 2016;Rapoport et al, 2017;Cranford-Smith & Huber, 2018). SecA acts a monomer and uses the energy of ATP hydrolysis to move its substrates through the protein-conducting SecY channel (Economou & Wickner, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Exhaustive biochemical and structural studies from numerous laboratories have revealed the essential features of SecA structure and function at the molecular level (see review by Crane and Randall 4 ), although the structural details of its interactions with the SecYEG translocase are just now beginning to emerge. 5 Since the first structure of SecA from Bacillus subtilis, 6 structures of SecA from several species have been determined (see reviews 7,8 ) and suggest, along with biochemical studies, 9,10 that SecA is dimeric in the cytoplasm. However, little is known about SecA conformational states in the cytoplasm of E. coli, which are important for understanding in vivo conformational transitions that occur during secretion of preproteins across the inner membrane.…”
mentioning
confidence: 99%
“…The former mutation dramatically decreased the VemP arrest efficiency, whereas the latter mutation did not; thus, specific interactions exist between the VemP nascent chain and the interior of the exit tunnel of the ribosome, and the interaction mode of VemP is different from that of SecM (6). However, the mechanism via which the conserved segment inactivates the peptidyl transfer center (PTC) 2 of the ribosome remains unclear.…”
mentioning
confidence: 99%